Comparison of epidemiology, treatments, and outcomes in pediatric versus adult ependymoma. Issue 1 (21st February 2020) - Elsamadicy, Aladine A; Koo, Andrew B; David, Wyatt B; Lee, Victor; Zogg, Cheryl K; Kundishora, Adam J; Hong, Christopher S; DeSpenza, Tyrone; Reeves, Benjamin C; Kahle, Kristopher T; DiLuna, Michael
Abstract: Background: Mounting evidence supports the presence of heterogeneity in the presentation of ependymoma patients with respect to location, histopathology, and behavior between pediatric and adult patients. However, the influence of age on treatment outcomes in ependymoma remains obscure. Methods: The SEER database years 1975–2016 were queried. Patients with a diagnosis of ependymoma were identified using the International Classification of Diseases for Oncology, Third Edition, coding system. Patients were classified into one of 4 age groups: children (age 0–12 years), adolescents (age 13–21 years), young adults (age 22–45 years), and older adults (age >45 years). The weighed multivariate analysis assessed the impact of age on survival outcomes following surgical treatment. Results: There were a total of 6076 patients identified with ependymoma, of which 1111 (18%) were children, 529 (9%) were adolescents, 2039 (34%) were young adults, and 2397 (40%) were older adults. There were statistically significant differences between cohorts with respect to race ( P < .001), anatomical location ( P < .001), extent of resection ( P < .001), radiation use ( P < .001), tumor grade ( P < .001), histological classification ( P < .001), and all-cause mortality ( P < .001). There was no significant difference between cohorts with respect to gender ( P = .103). On multivariate logistic regression, factors associated with all-cause mortality rates included males (vs females), supratentorial location (vs spinal cord tumors), and radiation treatment (vs no radiation). Conclusions: Our study using the SEER database demonstrates the various demographic and treatment risk factors that are associated with increased rates of all-cause mortality between the pediatric and adult populations following a diagnosis of ependymoma.